PENGARUH ORIENTASI KEWIRAUSAHAAN, KNOWLEDGE MANAGEMENT, DAN STRATEGI KEMITRAAN TERHADAP KEUNGGULAN BERSAING SERTA IMPLIKASINYA PADA KINERJA PERUSAHAAN (Studi Pada UMKM Kerajinan Logam Kecamatan Cepogo Kabupaten Boyolali) - Muchtar, Muliasari Kurniati; Miyasto, Miyasto; Rahardja, Edy (JURNAL BISNIS STRATEGI, 2018)
This research was conducted to develop a model to analyze the effect of entrepreneurial orientation, knowledge management, strategic partnership to competitive advantage as well as its implications on the performance of the company. The research problem posed is a decrease in production value and investment value along with the increasing number of metal craft business units in Cepogo, Boyolali Regency. The purpose of this study was to determine and analyze the entrepreneurial background, knowledge management and partnership strategies to competitive advantage and business performance. To test and analyze the performance excellence of enterprises. This research was conducted on the owners of SMEs which are in Sub Cepogo Boyolali, using a survey of 229 sample survey. Using Structural Equation Modeling (SEM) in AMOS software program version 23. Results from seven hypotheses show entrepreneurial orientation, knowledge management, and partnership strategies positive and significant competitive advantage. Entrepreneurial orientation, knowledge management, and competitive advantages positive and significant impact on business performance. Partnership strategy does not affect the performance of the business.